Driving Forces of European Landscape Change - Matt, Gordon (Jihočeská univerzita, 2021)
This master's thesis examines driving forces of landscape change in the Wadden Sea region. The region is a UNESCO World Natural Heritage site and encompasses North Sea coasts of Denmark, Germany and the Netherlands. The cultural landscape has faced change for millennials. The socioeconomic, technological, political and institutional, cultural as well as natural driving forces of these changes were analyzed in this thesis with the help of systematic review. Historical overviews were presented, and new, emerging trends identified.
Driving Forces of European Landscape Change
Keywords: landscape change; driving forces; proximate and underlying drivers; landscape; landscape history; cultural landscape; nature; landscape identity; energy transition; nature conservation; landscape change; driving forces; proximate and underlying drivers; landscape; landscape history; cultural landscape; nature; landscape identity; energy transition; nature conservation